Analisis Pesan Dakwah Serial Animasi Nussa Season 1 di YouTube Little Giantz dalam Mengajarkan Pemahaman Tentang Akhlak pada Anak - Indah Febriyanti; Nurseri Hasnah Nasution; Emi Puspita Dewi (ScidacPlus, 2024)
The script is titled “Analysing Da’wah Message of Nussa Animation Series Season 1 on YouTube Little Giantz in Teaching Understanding of Aklak to Anak” aimed at knowing the da’wah message in Nussa animation as well as knowing the da’wah message in teaching children’s understanding of Aklak. The research method used is Roland Barthes’ semiotic analysis method because it is classified as suitable enough to analyze the Nussa animation series’ da’wah elements, denotations and connotations. Research uses observation and documentation data collection techniques. The result is that the da’wah message found in the study contains the message of faith, sharia, and scripture. Furthermore, the da’wah message taught about the scripture is to say thank you, please help, apologize, sincerely, kindly, patient. Advice for parents should be able to choose which animation shows are worth watching, and pay attention to the meaning of animation shows, because animation shows can be an effective learning medium by viewing, listening to and observing the message content of those animations, and then we can apply them to everyday life. And don’t watch animated shows that contain negative things to avoid bad things.